A molecular gradient along the longitudinal axis of the human hippocampus informs large-scale behavioral systems - Jacob W. Vogel (Nature Portfolio, 2020)
The human hippocampus plays a role in many different cognitive systems. Here the authors find that a single pattern of brain gene expression can predict how different parts of the hippocampus interact with the rest of the brain.